1999
DOI: 10.1071/a98106
|View full text |Cite
|
Sign up to set email alerts
|

Detection and differentiation of phytoplasmas in Australia: an update

Abstract: Phytoplasmas were found in 33 plant species that were not described as host plants in an earlier Australian survey. Plants displayed characteristic symptoms of little leaf, proliferation, and floral abnormalities. Restriction fragment length polymorphism analysis revealed 13 different restriction patterns. The majority of phytoplasmas showed a restriction pattern identical to that of either the tomato big bud (TBB) or sweet potato little leaf V4 (SPLL-V4) phytoplasma. Phytoplasmas from 6 plant species showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 17 publications
7
60
1
1
Order By: Relevance
“…This is in contrast to previous disease surveys in northern Australia, which showed that the SPLL-V4 phytoplasma is associated with diseases that occur in a wide range of plant species (Davis et al , 2003Schneider et al 1999;Padovan and Gibb 2001). The identification of a single plant species positive for the SPLL-V4 phytoplasma compared with the TBB phytoplasma (16 species) suggests that in south-east Queensland, these phytoplasmas may not have a common vector and that the vector for the SPLL-V4 phytoplasma is not prevalent.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…This is in contrast to previous disease surveys in northern Australia, which showed that the SPLL-V4 phytoplasma is associated with diseases that occur in a wide range of plant species (Davis et al , 2003Schneider et al 1999;Padovan and Gibb 2001). The identification of a single plant species positive for the SPLL-V4 phytoplasma compared with the TBB phytoplasma (16 species) suggests that in south-east Queensland, these phytoplasmas may not have a common vector and that the vector for the SPLL-V4 phytoplasma is not prevalent.…”
Section: Discussioncontrasting
confidence: 53%
“…In Australia, Ca. P. australiense is also associated with the diseases strawberry green petal (SGP) (Padovan et al 2000b), papaya dieback (PDB; Gibb et al 1996;Liu et al 1996), Australian grapevine yellows (AGY; Padovan et al 1996) and mung bean witches' broom (MBWB; Schneider et al 1999). More recently, Ca.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phytoplasma brasiliense" in a Sterculiaceae tree species. Previous reports of phytoplasmas in a Sterculiaceae weed species, Waltheria indica, were done in Brazil (Kitajima & Costa, 1971) and Australia (Schneider et al, 1999;Wilson et al, 2001); the last of these belonged to group 16SrII (Gen Bank accession Y15870).…”
mentioning
confidence: 99%